The Mother and the Law - Griffith, D. W.; Bitzer, Gottfried W.; Marsh, Mae; Harron, Robert; Cooper, Miriam (Eureka Video, 2014)
After D.W. Griffith's masterpiece "Intolerance" failed at the box office, two of the four tales that make up that movie were extracted and released as their own separate features to try to recoup more money. In the case of "The Woman and the Law", the "modern day" segment, this is ironically fitting, since it was originally conceived as an independent feature before Griffith got the idea of incorporating it into a frame tale. It opens with the Ludlow Massacre but is otherwise a fictional tale, chronicling a man and woman who cannot seem to escape the lower class. One sequence, involving the interference of social workers in the integrity of a family, is wrenching and remains relevant today. Though good, "The Mother and the Law" is best seen in "Intolerance", where the concurrent telling of three other tales adds power to the impact of this one. [www.rinkworks.com]
Keywords: Blu-Ray-Disc